KETERCAPAIAN PERKEMBANGAN RELIGIUS BESERTA PERMASALAHANNYA DI SMP MUHAMMADIYAH 1 DAN MUHAMMADIYAH 2 PEKANBARU - Chantika Banjar Getih; Zulfan Saam; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak : The title of this research is Achievement of Religious Development along with its problems in SMP Muhammadiyah 1 and Muhammadiyah 2 Pekanbaru. This study aims to determine whether the development of religus Smp students has been achieved or not. Does the problem in religious development affect student achievement and to see if there is a difference in the attainment of religious development between one Smp and another Smp. The method used is Descriptive Quantitative. Sampling in this research is done by Probability Sampling technique. Research data is obtained through questionnaire and documentation. The results of this study show that the achievement of religious development in SMP Muhammadiyah 1 and SMP Muhammadiyah 2 Pekanbaru has been achieved which indicator is in accordance with the task of religious development of Sunaryo Kartadinata theory that is a) Praying and Praying, b) Learning Religion, c) Faith and d) Forbearance. Keywords: Development, Problems, Religious